2000
DOI: 10.1007/s001670000130
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stability after ACL injury: who can hop?

Abstract: Single-leg hops are used clinically to assess knee function in patients following anterior cruciate ligament (ACL) rupture and reconstruction. Researchers study ACL-deficient individuals in order to identify movement strategies in the absence of a major knee stabilizer, thereby providing information to clinicians regarding treatment options. Single-leg hops represent an activity which places higher demands on the knee than walking or jogging. Hops are thought by some to represent demands that are more comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
284
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(301 citation statements)
references
References 19 publications
14
284
0
3
Order By: Relevance
“…It is well supported in the literature that quadriceps strength is highly correlated with good outcome post ACL reconstruction [63][64][65][66] and deficits in quadriceps strength are associated with low self-reported function and performance measures [67]. Deficits on quadriceps strength have been shown to predict performance based functions better than other factors, like graft type, knee pain or asymptomatic knee [67].…”
Section: Muscle Strengthmentioning
confidence: 92%
See 2 more Smart Citations
“…It is well supported in the literature that quadriceps strength is highly correlated with good outcome post ACL reconstruction [63][64][65][66] and deficits in quadriceps strength are associated with low self-reported function and performance measures [67]. Deficits on quadriceps strength have been shown to predict performance based functions better than other factors, like graft type, knee pain or asymptomatic knee [67].…”
Section: Muscle Strengthmentioning
confidence: 92%
“…The most commonly used tests known for their reliability are the 4 available hop tests (single hop, triple hop, crossover hop and timed hop test) [9,[93][94][95][96]. All these tests can assess the functional performance and the neuromuscular control of an individual by imitating the high demands of the knee during high level activities [65,94,97,98]. Taking the results of these 4 hop tests Limb Symmetry Index (LSI) is calculated for each test separately.…”
Section: Neuromuscular Control/functional Readinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Research using biomechanical measurements of the hip, ankle, and knee joint, and electromyographical measurements of the musculature in the lower extremities shows that, biomechanically speaking, all people move differently. Research results show no constant or reliable difference in movement strategies between patients who sustain an ACL injury and persons not injured (Rudolph, Axe, & Snyder-Mackler, 2000). However, some research has shown differences in movement patterns and muscular activity in the legs during walking, running, and jumping following ACL injury (Rudolph et al, 2000).…”
mentioning
confidence: 95%
“…Research results show no constant or reliable difference in movement strategies between patients who sustain an ACL injury and persons not injured (Rudolph, Axe, & Snyder-Mackler, 2000). However, some research has shown differences in movement patterns and muscular activity in the legs during walking, running, and jumping following ACL injury (Rudolph et al, 2000). Fitzgerald and Kelley (2000) claim that there is a limited understanding of the role of neuromuscular control mechanisms play in maintaining knee stability.…”
mentioning
confidence: 99%